1996
DOI: 10.1071/rd9960287
|View full text |Cite
|
Sign up to set email alerts
|

Metacarpal growth and systemic markers of bone metabolism in the ovine fetus

Abstract: Bone metabolism was assessed in 56 Ile de Francex(RomanovxLimousine) fetal lambs killed between Day 80 and Day 145 of gestation. In each fetus, the length, width and weight, as well as the calcium and phosphorus content of the left diaphyseal metacarpal bone were measured. Plasma alkaline phosphatase (ALP) and tartrate-resistant acid phosphatase (TRAP) activities, bone ALP (B-ALP), osteocalcin (OC) and insulin-like growth factor-I (IGF-I) were assayed in these fetuses and in six newborn lambs from birth until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It was reported that goats showed a more accelerated bone remodelling that sheep, which was demonstrated by ICTP, CTx (LIESEGANG et al, 2003), BALP (LIESEGANG et al, 2003;SOUSA et al, 2014a), and OC determinations in various studies (PASTOUREAU et al, 1991;LIESEGANG et al, 2003). Collignon et al (1996) demonstrated that bone growth since the fetal stage produces alterations in serum OC and BALP, confirming the usefulness of these markers in bone formation and growth. Scott et al (1997) reported that OC, BALP, DPD, and PYD may be useful for detection of changes in bone growth caused by deficient diets, and Wan Zahari et al (1994) reported that high phosphorus diets resulted in increased bone resorption (increased TRAP) in lambs.…”
Section: Exercisementioning
confidence: 81%
“…It was reported that goats showed a more accelerated bone remodelling that sheep, which was demonstrated by ICTP, CTx (LIESEGANG et al, 2003), BALP (LIESEGANG et al, 2003;SOUSA et al, 2014a), and OC determinations in various studies (PASTOUREAU et al, 1991;LIESEGANG et al, 2003). Collignon et al (1996) demonstrated that bone growth since the fetal stage produces alterations in serum OC and BALP, confirming the usefulness of these markers in bone formation and growth. Scott et al (1997) reported that OC, BALP, DPD, and PYD may be useful for detection of changes in bone growth caused by deficient diets, and Wan Zahari et al (1994) reported that high phosphorus diets resulted in increased bone resorption (increased TRAP) in lambs.…”
Section: Exercisementioning
confidence: 81%
“…It was reported that goats showed a more accelerated bone remodelling that sheep, which was demonstrated by ICTP, CTx (LIESEGANG et al, 2003), BALP (LIESEGANG et al, 2003;SOUSA et al, 2014a), and OC determinations in various studies (PASTOUREAU et al, 1991;LIESEGANG et al, 2003). Collignon et al (1996) demonstrated that bone growth since the fetal stage produces alterations in serum OC and BALP, confirming the usefulness of these markers in bone formation and growth. Scott et al (1997) reported that OC, BALP, DPD, and PYD may be useful for detection of changes in bone growth caused by deficient diets, and Wan Zahari et al (1994) reported that high phosphorus diets resulted in increased bone resorption (increased TRAP) in lambs.…”
Section: Exercisementioning
confidence: 83%
“…It was reported that goats showed a more accelerated bone remodelling that sheep, which was demonstrated by ICTP, CTx (LIESEGANG et al, 2003), BALP (LIESEGANG et al, 2003;SOUSA et al, 2014a), and OC determinations in various studies (PASTOUREAU et al, 1991;LIESEGANG et al, 2003). Collignon et al (1996) demonstrated that bone growth since the fetal stage produces alterations in serum OC and BALP, confirming the usefulness of these markers in bone formation and growth. Scott et al (1997) reported that OC, BALP, DPD, and PYD may be useful for detection of changes in bone growth caused by deficient diets, and Wan Zahari et al (1994) reported that high phosphorus diets resulted in increased bone resorption (increased TRAP) in lambs.…”
Section: Exercisementioning
confidence: 83%